2008
DOI: 10.1501/sporm_0000000127
|View full text |Cite
|
Sign up to set email alerts
|

Farkli Sevi̇yedeki̇ Li̇glerde Oynayan Takimlarin Altyapisinda Mücadele Eden Genç Futbolcularda Supramaksi̇mal Bacak Egzersi̇zi̇ Yanitlarinin Karşilaştirilmasi

Abstract: Bu çalışma farklı seviyedeki liglerde oynayan takımların altyapısında mücadele eden genç profesyonel futbol oyuncularında (1.lig altyapı ve 2.lig altyapı) supramaksimal bacak egzersizi (Wingate Test) sonrası ortaya çıkan güç değerlerinin ve test sonrası zirve laktik asit miktarının karşılaştırılması amacıyla yapılmıştır. Çalışmaya 1.lig altyapı takımından 10, 2.lig altyapı takımından 10 olmak üzere toplam 20 genç erkek futbolcu gönüllü olarak katılmıştır. Wingate testi sonrasında Zirve Güç (ZG), Ortalama Güç (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although the significant difference between measurement times of eight week-long training was detected, there was no significant difference between groups. Alemdaroglu et al (2008) found no statistically significant difference between peak strength (PS) and mean strength (MS) in values of strength variables obtained from WanT. Colakoglu and Karacan (2016) found a statistically significant increase in anaerobic strength values of young and middle-aged women.…”
Section: Discussionmentioning
confidence: 95%
“…Although the significant difference between measurement times of eight week-long training was detected, there was no significant difference between groups. Alemdaroglu et al (2008) found no statistically significant difference between peak strength (PS) and mean strength (MS) in values of strength variables obtained from WanT. Colakoglu and Karacan (2016) found a statistically significant increase in anaerobic strength values of young and middle-aged women.…”
Section: Discussionmentioning
confidence: 95%
“…USA) electroenzymatically with no processing. The analyzer was calibrated every test day in line with the manufacturing firm's guidance (Alemdaroğlu et. al, 2008).…”
Section: Determination Of Lactic Acid Concentrationmentioning
confidence: 99%